Rancang Bangun Aplikasi Pembuatan Laporan Keuangan Lembaga Pengelola Dana Zakat Infak Sedekah Berdasarkan PSAK 109 Pada YDSF Surabaya - Tamara, Nada Evi; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
Foundation Fund Sosial Al-Falah (YDSF) is one of the zakat fund management institutions infaq/charity in Indonesia, precisely located in the city of Surabaya, which is an utilization institution of communities funds and has more than 220.564 benefactor from the private circles and the communities general. YDSF provide information to the communities in the form of financial statements that are presented in a monthly magazine. For the time being financial statements are presented each month in the magazine has not been explain in detail on the type of fund receipts collected and the amount of type of distribution that occurs. Responsibility for the financial statements conducted YDSF can lead to decreased values of accountability as an fund management institution of communities. Based on these problems, YDSF as amil zakat institutions should perform its functions is public accountability the financial statements, need a making application financial reporting zakat infaq/charity based on the PSAK 109. By using PSAK 109 on the reports generated by the system, YDSF can accountable to the public so that receipts and distribution YDSF to be transparent with the details financial statements of the which attached based on each type of fund, among others zakat funds, infaq funds, waqf funds, non halal funds, and amil funds. As for the reporting that have been generated by the system based on the PSAK 109, among others, statements of financial position, statements of changes in funds, reports assets under management, and cash flow statements.